Analisis Kinerja Petugas Aviation Security Terhadap Pengawasan & Keamanan Penumpang Di Terminal Domestik Bandar Udara Internasional Yogyakarta - Christian Nanda Praptama; You She Melly Anne Dharasta (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
Yogyakarta International Airport is a replacement for Adiscipto Airport which is considered unable to accommodate many passengers so that a larger airport is built, it can have an influence on the performance of aviation security personnel on the supervision and security of passengers so that security and guarding of passengers at the airport terminal can be maintained from people who commit violations or acts against the law in the airport environment. The research that researchers use is a study using qualitative methods using data collection techniques of observation, interviews, literature studies and documentation, analysis techniques using data reduction, data presentation, conclusion drawing and validity testing using triangulation. Based on the quality of officers able to carry out supervisory duties, the quantity of officers is in accordance with the needs because it is assisted by CCTV and helps each other to back up, the timeliness of officers must arrive on time because there is a briefing, for the effectiveness of the load is sufficient depending on the officer, it needs supervision from the company and officers know for areas that must be guarded and officers will coordinate with related parties for guarding there are inspection lanes, WTMD, HHMD, checkpoints and Sageway, HT, and patrol cars for patrols. The performance of Aviation Security officers in conducting surveillance & passenger security is good according to applicable regulations which are used as the basis for performing duties at airports and the readiness of officers in conducting surveillance & passenger security at Yogyakarta International Airport aviation security officers already have and use adequate facilities in conducting surveillance and passenger security.